Strategic airport planning - Brown, Mike (New York, NY : Routledge, 2022)
"The aim of the book is to articulate a new approach to airport planning that better captures the complexities and velocity of change in our contemporary world. As a result, it will lead to higher performing airports for users, business partners, investors and other stakeholders. This is especially pertinent since airports will need to come back better from the Covid-19 pandemic. The book explains the importance of articulating a clear strategy, based on a rigorous analysis of the competitive landscape while avoiding the pitfalls of ambiguity and 'virtue signalling'. Having done so, demand forecasts can be developed that resemble S-curves, not simple straight lines, that reflect strategic opportunities and threats from which a master plan can be developed to allocate land and capital in a way that maximizes return on assets and social licence. The second distinctive feature of this book is the premise that planning an airport as an island, a fortress even, does not work anymore given how interconnected airports are with other components of the transportation system, the economies and communities they serve and the rapid pace of social and technological change. In summary, the book argues that airport planning needs to move beyond its traditional boundaries. The book is replete with real examples from airports of all sizes around the world and includes practical advice and tools for executives and managers. It is recommended reading for individuals working in the airport business or the broader air transport industry, members of airports' board of directors, who may be new to the business, elected officials, policy makers and urban planners in jurisdictions hosting or adjacent to airports, regulators, economic development professionals and, finally, students"--
OCLC-licensed vendor bibliographic record.
Keywords: Airports -- Economic aspects; Airports -- Planning; Strategic planning; TRANSPORTATION / Aviation / General; TRANSPORTATION / Aviation / Commercial; BUSINESS & ECONOMICS / Industries / Transportation